KEMAMPUAN MEMAHAMI PERCAKAPAN MENGGUNAKAN BAHASA INDONESIA BAGI MAHASISWA ASING DI UIN WALISONGO SEMARANG - Maya Rini Handayani (At-Taqaddum, 2018)
This article discusses the understanding of conversation skills using Bahasa. Respondents of this article were foreign students from South Thailand. They registered in UIN Walisongo Semarang in various departments and academic years. The ability to listen Bahasa was an indicator in this research. The 37 respondents were students from 2012 till 2016, who aged between 20 to 28 years old. The 25 students were female while the 12 others were male students. Data were collected using questionnaires. The article result shows that the average of students’ ability to listen Bahasa is in score 20. This score is 19 to 20, it occupied in the medium category. The category used five standard intervals, namely very high, high, medium, low, and very low. The summary of this research is the understanding the skill of conversation of foreign students using Bahasa is in a medium category.